2008
DOI: 10.1002/pd.1957
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12s in maternal serum as a potential marker of pre‐eclampsia

Abstract: ADAM12s in addition to being a potential marker of aneuploidy may also be a marker of pre-eclampsia. Further studies are required to see if this can improve on the clinical discrimination already provided by PAPP-A in the early first trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 25 publications
3
59
1
Order By: Relevance
“…6,17,18 Our findings regarding ADAM12 support a previous study indicating that ADAM12 does not provide useful prediction of SGA, pre-eclampsia or preterm delivery 19 and contradict two previous reports showing that in pregnancies developing pre-eclampsia the serum ADAM12 concentration is reduced. 1,2 We only found a small, although significant, reduction of ADAM12 levels in pregnancies complicated by pre-eclampsia who subsequently delivered a SGA neonate. This may be explained by the fact that ADAM12 is a placental product involved in the control of fetal growth.…”
Section: Markermentioning
confidence: 83%
See 1 more Smart Citation
“…6,17,18 Our findings regarding ADAM12 support a previous study indicating that ADAM12 does not provide useful prediction of SGA, pre-eclampsia or preterm delivery 19 and contradict two previous reports showing that in pregnancies developing pre-eclampsia the serum ADAM12 concentration is reduced. 1,2 We only found a small, although significant, reduction of ADAM12 levels in pregnancies complicated by pre-eclampsia who subsequently delivered a SGA neonate. This may be explained by the fact that ADAM12 is a placental product involved in the control of fetal growth.…”
Section: Markermentioning
confidence: 83%
“…Previous studies have reported that in the first-trimester concentrations are reduced for placental protein 13 (PP13), anti-angiogenic factors such as placental growth factor (PlGF) and a desintegrin and metalloproteinase 12 (ADAM12) in pregnancies with early-onset pre-eclampsia (delivery before 34 weeks of gestation) and pre-eclampsia later in pregnancy, with a higher predictive value in the former group. [1][2][3][4][5][6] However, the number of cases studied for early-onset pre-eclampsia was generally low, ranging from 6 to 34. Recently, a detection rate of 86% of early-onset pre-eclampsia has been predicted at a false-positive rate of 10%, by combining maternal characteristics, obstetrics history, serum PlGF and uterine artery pulsatility index at 11-14 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, decreased serum levels of ADAM12, another member of ADAM family, have been reported in PE. 47,48 In addition, multiple ADAMTS subtypes have been detected, albeit many at low levels, in total RNA lysates prepared from human term placenta or uterine tissues, suggesting that these metalloproteinases may play important roles in implantation and placentation. 49 A spliced form (2.4 kb of mRNA) of ADAMTS13 has also been identified in placenta, but the expression of the protein in the placenta or any specific cell in placenta has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…26 Laigaard et al and Spenceret al have shown reduced ADAM12 levels in pregnancies complicated by PE, and in both studies ADAM12 was suggested to be a potential PE marker(median ADAM12 MoM were 0.86, P = 0.008 and 0.49 P = 0.0001, respectively). 27 In contrast, Poonet al, and…”
mentioning
confidence: 95%